2014
DOI: 10.1055/s-0034-1388020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian-hormone levels during pregnancy and postpartum

Abstract: Background: The number of unintentionally childless couples is increasing as more couples seek to conceive for the first time in the third or fourth decade of the woman's life. Determination of ovarian reserve is an essential component of infertility assessment. The Anti-Müllerian-Hormone (AMH) seems to be the most reliable predictor of ovarian reserve. In this study we analyzed AMH in a cohort of pregnant women without fertility impairment to determine age-dependent decline and possible AMH fluctuations durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Viability of a natural pregnancy was not associated with increasing or decreasing AMH levels. The trend for decreasing AMH levels in natural pregnancies is similar to that reported by other investigators (11,13). There is increasing evidence that adequate long-term gonadotropins are required for AMH (6,(25)(26)(27), and the suppression of gonadotropins that occurs during early pregnancy, and persists until postpartum, may in part explain the trend for reducing AMH levels noted in some of our early natural pregnancies and in pregnancies in general (11,13).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Viability of a natural pregnancy was not associated with increasing or decreasing AMH levels. The trend for decreasing AMH levels in natural pregnancies is similar to that reported by other investigators (11,13). There is increasing evidence that adequate long-term gonadotropins are required for AMH (6,(25)(26)(27), and the suppression of gonadotropins that occurs during early pregnancy, and persists until postpartum, may in part explain the trend for reducing AMH levels noted in some of our early natural pregnancies and in pregnancies in general (11,13).…”
Section: Discussionsupporting
confidence: 88%
“…However, when assessing longitudinal trends in individual women, different patterns of changing AMH levels were observed. Two welldesigned studies (11,13) report a decrease in AMH levels with advancing gestational age. Cross-sectional studies of AMH are limited by the fact that different women of the same age can show substantial variations in their AMH levels (9,11,24); however, the study conducted by Nelson et al (13) was important in confirming longitudinal changes in the same cohort of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in relation to pregnancy, in the only longitudinal study available (n=60) a significant decrease in AMH levels was found in the 2 nd and 3 rd trimesters compared to the 1 st trimester, with a mean reduction at the end of pregnancy of about 50% (Nelson et al, 2010). Such a decline in AMH levels during pregnancy has been recently confirmed by Köninger et al (2013) in a cross-sectional study. While this no doubt reflects reduced follicular maturation, there may also be a contribution of pregnancy-associated haemodilution and increased plasma-protein binding.…”
Section: Variability Of Serum Amh In Normal Womenmentioning
confidence: 60%
“…The probability of breastfeeding did not, however, demonstrate a strong class trend in relation to AMH. Several studies have reported a suppressive effect of pregnancy on the ovarian reserve (Gerli et al, 2015; Köninger et al, 2013; Nelson et al, 2010). The effect of breastfeeding is not previously described, although AMH was not reduced in women with hyperprolactinaemia-induced amenorrhea (Li, Anderson, Yeung, Ho, & Ng, 2011).…”
Section: Discussionmentioning
confidence: 99%